2020
DOI: 10.26434/chemrxiv.12751361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In Silico Docking Analysis Revealed the Potential of Phytochemicals Present in Phyllanthus Amarus and Andrographis Paniculata, Used in Ayurveda Medicine in Inhibiting SARS-CoV-2

Abstract: No therapeutics and vaccines are available against SARS-CoV-2 at present. In the current study we have made an attempt to provide preliminary evidences for interaction of 35 phytochemicals from two plants (<i>Phyllanthus amarus </i>and <i>Andrographis paniculata</i> used in Ayurveda<i>)</i> with SARS-CoV-2 proteins (S protein, 3CLpro, PLpro and RdRp) through <i>in silico</i> docking analysis. The docking was performed with the aid of AutoDock Vina and ADME and ot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A static failure analysis has been carried out on different joints like adhesive bonding, mechanical bolting, and bonded-bolted joints, and revealed that bonded-bolted joints have higher strength in terms of joint strength [17][18]. Non-destructive testing based techniques are used to uncover the faults in the aviation materials, such as their efficacy in detecting and identifying, locating, and characterising damage in the early stages, to extend the life and monitor the health of the structures [19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A static failure analysis has been carried out on different joints like adhesive bonding, mechanical bolting, and bonded-bolted joints, and revealed that bonded-bolted joints have higher strength in terms of joint strength [17][18]. Non-destructive testing based techniques are used to uncover the faults in the aviation materials, such as their efficacy in detecting and identifying, locating, and characterising damage in the early stages, to extend the life and monitor the health of the structures [19][20].…”
Section: Introductionmentioning
confidence: 99%